1992
DOI: 10.1085/jgp.100.5.803
|View full text |Cite
|
Sign up to set email alerts
|

Proton currents through amiloride-sensitive Na channels in hamster taste cells. Role in acid transduction.

Abstract: A B S T R A C T The activity of taste cells maintained in the intact hamster tongue was monitored in response to acid stimulation by recording action currents from taste receptor cells with an extraceUular "macro" patch pipette: a glass pipette was pressed over the taste pore of fungiform papillae and perfused with citric acid, hydrochloric acid, or NaC1. Because this technique restricted stimulus application to the small surface area of the apical membranes of the taste cells, many nonspecific, and potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
89
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(102 citation statements)
references
References 45 publications
12
89
0
1
Order By: Relevance
“…As was observed previously, s study of Xenopus oocytes showed a depolarization of the membrane potential by fertilization, which will induce Na + entry into the cell [20]. It was also found that the proton current can flow through (amiloridesensitive) Na + channels in the hamster taste cells [21]. Taken together, these findings lead us to speculate that a protocol of acidic stimulation (as Obokata et al did for reprogramming [1]) will induce Na + entry, which will induce an increase in intracellular proton level initially; then the water state will be changed gradually from the bound state to the free state, which will initiate a new cell cycle as described above.…”
Section: Cell-cycle Changes In the Intracellular Water Propertiessupporting
confidence: 59%
“…As was observed previously, s study of Xenopus oocytes showed a depolarization of the membrane potential by fertilization, which will induce Na + entry into the cell [20]. It was also found that the proton current can flow through (amiloridesensitive) Na + channels in the hamster taste cells [21]. Taken together, these findings lead us to speculate that a protocol of acidic stimulation (as Obokata et al did for reprogramming [1]) will induce Na + entry, which will induce an increase in intracellular proton level initially; then the water state will be changed gradually from the bound state to the free state, which will initiate a new cell cycle as described above.…”
Section: Cell-cycle Changes In the Intracellular Water Propertiessupporting
confidence: 59%
“…Action potential firing appears to be one important step in the transduction and signaling of sensory information in taste buds. For example, the frequency of spike discharge is related to the concentration of certain stimuli (Gilbertson et al, 1992;Cummings et al, 1993). In addition, membrane depolarization during action potential seems to be necessary to activate Ca 2ϩ channels for neurotransmitter release underlying signal transfer to afferent nerves (Béhé et al, 1990;Furue and Yoshii, 1997).…”
Section: Abstract: Development; Taste Cells; Membrane Excitability; mentioning
confidence: 99%
“…Action potential discharges are regularly recorded from taste cells during chemostimulation in mammals (Béhé et al, 1990;Avenet and Lindemann, 1991;Gilbertson et al, 1992;Cummings et al, 1993;Furue and Yoshii, 1997;Ohtubo et al, 2001). Given the presence of voltage-gated Na ϩ currents, Na/OUT cells are able to fire action potentials (see below).…”
Section: Development Of Membrane Properties In Na/out Cellsmentioning
confidence: 99%
“…Taste cells express several proton-gated or proton-permeant cation channels that have been proposed to be sour taste transducers, including cation channels (ENaCs, MDEG1, ASIC-2b: Gilbertson and Gilbertson 1994;Gilbertson et al 1992;Liu and Simon 2001;Ugawa et al 1998), hyperpolarization-activated cyclic nucleotidegated channels (HCNs: Stevens et al 2001), and protonsensitive chloride channels (Miyamoto et al 2000). However, even though most of these ion channels are expressed in subsets of taste cells, it is not known whether these cells are the same cells that mediate acid taste.…”
Section: Introductionmentioning
confidence: 99%